Saddle pulmonary embolism and clot in transit in COVID-19 infection: a case report of catastrophic venous thromboembolism. Issue 6 (7th December 2020) - Aoi, Shunsuke; Kakkar, Amit M; Golowa, Yosef; Grushko, Michael; Coyle, Christina M; Elrafei, Tarek; Langston, Matthew D; Faillace, Robert T; Bangalore, Sripal; Sokol, Seth I
Abstract: Background : Coronavirus disease 2019 (COVID-19) is associated with a coagulopathy favouring thrombosis over bleeding that imparts a poor prognosis. Clot in transit (CIT) is considered a rare entity and the most severe form of venous thromboembolism (VTE), carrying a higher mortality than isolated pulmonary embolism (PE). The incidence of this phenomenon in patients with COVID-19 infection is unknown and likely under-recognized. Case summary : During the peak of the COVID-19 pandemic in New York City, a 70-year-old Hispanic female presented with syncope due to a saddle PE further complicated by a highly mobile CIT. Polymerase chain reaction was positive for COVID-19 infection, however, there was no evidence of lung parenchymal involvement or hyper-inflammation. Based on consensus from a multidisciplinary team, aspiration thrombectomy was attempted to treat this extreme case of VTE, however, the patient died during the procedure. Discussion : This case raises awareness to the most catastrophic form of VTE, presenting in an early phase of COVID-19 infection without the typical hyper-inflammation and severe lung injury associated with development of COVID-related coagulopathy. It also serves to inform on the critical role echocardiography has in the comprehensive evaluation and re-evaluation of hospitalized patients with COVID-19, and the importance of a multidisciplinary organized approach in clinical decision-making for this complex and poorly understood disease and its sequelae.